Stability amidst student protests? Evaluating the strength of racially diverse social systems through Bronfenbrenner’s theoretical lens - WP Wahl; Kingsley Chinaza Nwosu (Perspectives in Education)
The complexity of race-related student protests is a challenge facing universities worldwide. Race-related protests disrupted a university campus in central South Africa in February 2016. These protests allowed the institution to evaluate how interpersonal relations amongst diverse students in residences activated its prior support function in the face of a campus crisis. Although a considerable number of researchers have utilised Bronfenbrenner’s ecological systems theory to analyse the influence of peer interaction on student success, various shortcomings have made it difficult to derive a good understanding of the destabilising effect of a campus crisis on the developmental ecology of university campuses – something this study aimed to address. Purposive sampling was used to select participants for 14 focus group discussions immediately after the 2016 protest period. A thematic content analysis identified three overarching themes: enclosure versus exposure, communication and crisis, and discomfort and support. The study findings concluded that the interpersonal relations amongst diverse students can continue to enhance the developmental ecology of campuses challenged by the destabilising effect of race-related protests if specific principles are upheld during the unrest.